2021
DOI: 10.3389/fmed.2021.731421
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Spontaneous Regression of Retinopathy of Prematurity in China: A 5-Year Retrospective Case Series

Abstract: Purpose: The aim of this study is to explore the clinical features of spontaneous regression of retinopathy of prematurity (ROP) in China, including fundus appearance, time course, and affecting factors.Methods: Data of pediatric patients in whom ROP spontaneously regressed without treatment were collected, including general demographics, medical history, zones and stages of ROP, and changes of fundus appearance. The fundus manifestations of spontaneous regression in ROP were systematically summarized. Meanwhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, presence of retinal hemorrhage is also an inversely predictive factor for the spontaneous regression of ROP. Wang et al's [23] study also proved retinal hemorrhages was confirmed as dependent factors for delayed regression. In the case of retinal hemorrhages from a birth trauma, the mechanism of hemorrhage inducing, or aggravating ROP is still not clear.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, presence of retinal hemorrhage is also an inversely predictive factor for the spontaneous regression of ROP. Wang et al's [23] study also proved retinal hemorrhages was confirmed as dependent factors for delayed regression. In the case of retinal hemorrhages from a birth trauma, the mechanism of hemorrhage inducing, or aggravating ROP is still not clear.…”
Section: Resultsmentioning
confidence: 88%
“…This study aims to explore the predictive factors for severe ROP and to establish a nomogram for predicting severe ROP in southeast China. [14] . The International Classification of Retinopathy of Prematurity, Third Edition (ICROP3) [15] was used for diagnosis and staging of ROP.…”
Section: Introductionmentioning
confidence: 99%